Rancang Bangun Automatic Fish Feeder Berbasis Internet of Things (IoT) - Violla Gunova; Mahmud Idris (Politeknik Negeri Bengkalis, 2023)
Currently, a significant portion of fish feeding still relies on conventional methods involving manual or hand-feeding techniques. However, this manual approach proves to be less efficient due to its strong dependence on human labor. The emergence of information technology has paved the way for a more advanced solution: the potential for automated fish feeding conducted remotely through the utilization of the Internet of Things (IoT) framework. This application of IoT principles for fish feeding automation is executed using the NodeMCU ESP8266 as a microcontroller and transmitter-receiver devices for internet connectivity, a proximity sensor tasked with detecting the quantity of available feed, a servo motor employed to operate the feed valve lid, and the Blynk application employed for both control and monitoring of fish feed activities. The outcome for this project is an IoT-based Automatic Fish Feeder, purposefully designed for versatile deployment, functioning seamlessly from any location with access to the internet.